THE IMPACT OF THE TOURISM SECTOR ON ECONOMIC GROWTH AND LABOR ABSORPTION IN THE PROVINCE OF WEST NUSA TENGGARA - Agus Salihin (Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractThe purpose of this study was to determine the impact of the tourism sector on economic growth and labor absorption in the province of West Nusa Tenggara. This research includes quantitative research. The type of data used is secondary data including data on the number of tourist visits, data on economic growth and data on labor absorption from January 2018 to December 2020. Data collection techniques use documentation techniques. The data analysis test technique used a simple linear regression test. The results of the study can be explained that the tourism sector has a positive impact on economic growth and employment. When the tourism sector increased by 1%, economic growth increased by 0.45% and employment increased by 0.41%.Keywords: Tourism Sector, Economic Growth, Labor Absorption